Implementation of Sirekap in the 2024 Simultaneous Regional Elections at the East Java Provincial KPU - Angelina, Gabriel; Nawangsari, Ertien Rining (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
General Elections (Pemilu) and Regional Head Elections (Pilkada) are important elements in Indonesian democracy. The 2024 Simultaneous Pilkada in East Java presents challenges and innovations, including the implementation of the Electronic Recapitulation Information System (SIREKAP) as a tool for counting and recapitulating votes. This study aims to analyze the implementation of SIREKAP at the East Java Provincial KPU using George Edward III's implementation theory approach, which includes communication, resources, disposition, and bureaucratic structure. The research method uses a qualitative descriptive approach with primary data from interviews and observations, as well as secondary data from official KPU documents and related literature. The results of the study show that communication between KPU levels has been running effectively through technical guidance and digital media, although coordination constraints at the KPPS level are still found. The human resources and infrastructure of the East Java KPU are considered adequate, as seen from the achievement of 100% document uploads in the SIREKAP application. The disposition of the implementers shows a high commitment to supporting the success of this policy. A well-organized bureaucratic structure ensures optimal coordination between KPU levels. This study emphasizes the importance of improving training, allocating adequate resources, and developing a monitoring system to optimize the implementation of SIREKAP in the future.